2021
DOI: 10.1186/s12885-021-08463-7
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of circulating tumour cells (CTCs) and CTC white blood cell clusters in patients with renal cell carcinoma

Abstract: Purpose Circulating tumour cell (CTC) and CTC-white blood cell (CTC-WBC) clusters are related to the prognosis of tumour patients. However, the relationship between CTC-WBC clusters and prognosis in renal cell carcinoma (RCC) patients is not clear. We evaluated the prognostic value of CTC-WBC clusters using metastasis-free survival (MFS) and overall survival (OS) in patients with RCC. Materials and methods The baseline, survival, and CTC data of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…These results could help clinicians assess patient outcomes and develop treatment strategies. Similar findings have been demonstrated for advanced renal cell carcinoma (27,28), liver cancer (29), breast cancer, and gastric cancer (30,31). In addition, according to the combined analysis, patients with ≥7 CTCs and with CTC-WBC clusters had the highest risk of progression.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results could help clinicians assess patient outcomes and develop treatment strategies. Similar findings have been demonstrated for advanced renal cell carcinoma (27,28), liver cancer (29), breast cancer, and gastric cancer (30,31). In addition, according to the combined analysis, patients with ≥7 CTCs and with CTC-WBC clusters had the highest risk of progression.…”
Section: Discussionsupporting
confidence: 80%
“…At present, no general understanding exists regarding the frequency of CTC-WBC clusters in various cancer types. Previous studies have reported the frequency of patients positive for CTC-WBC clusters to be in the range of 3.4-41.6% (27,29,30). Meanwhile, in the present study, the frequency of these patients was 29.27%, which might be related to the tumor types and enrichment methods.…”
Section: Discussioncontrasting
confidence: 43%
“…The CanPatrol CTC analysis system used in this study is a novel method that enables the detection of CTC-WBC clusters as well as total CTCs and EMT phenotypes of CTCs ( 18 , 22 ). Using the membrane filtration method that does not rely on surface markers, this system can enrich a variety of CTC subtypes and the CTC-WBC cluster, followed by EMT typing of the enriched CTCs and the CTC-WBC cluster through the fluorescence-labeled epithelial or mesenchymal markers.…”
Section: Discussionmentioning
confidence: 99%
“…Szczerba et al [ 15 ] has revealed the role of neutrophils as escorts in the blood steam to promote the cell cycle progression and accelerate metastasis formation in the breast cancer model. Researches seeking the crosstalk between the tumor prognosis and CTC-WBC clusters have been conducted in several cancers, including those of breast [ 15 ], lung [ 16 ], renal [ 17 ], liver [ 18 ] and gastric [ 19 ], but absent for CRC.…”
Section: Introductionmentioning
confidence: 99%